2011
DOI: 10.1016/j.ajpath.2010.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Protein Tyrosine Phosphatase 1B (PTP1B) Deficiency Accelerates Hepatic Regeneration in Mice

Abstract: Protein tyrosine phosphatase 1B (PTP1B) is a key regulator of metabolism and cell growth by its ability to dephosphorylate tyrosine kinase receptors and modulate the intensity of their signaling cascades. Because liver regeneration involves tyrosine phosphorylation-mediated signaling, we investigated the role of PTP1B in this process by performing partial hepatectomy in wild-type (PTP1B ؉/؉ ) and PTP1B-deficient (PTP1B ؊/؊ ) mice. The expression of PCNA and cyclins D1 and E (cell proliferation markers) was enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 55 publications
3
25
2
Order By: Relevance
“…Protein tyrosine phosphatase 1B (PTP1B) is a key regulator of metabolism and cell growth by its ability to dephosphorylate tyrosine kinase receptors, including EGFR. In PTP1B null mice with partial hepatectomy, liver regeneration is enhanced due to activated EGFR signaling pathways (457).…”
Section: Role Of Egfr In the Livermentioning
confidence: 99%
“…Protein tyrosine phosphatase 1B (PTP1B) is a key regulator of metabolism and cell growth by its ability to dephosphorylate tyrosine kinase receptors, including EGFR. In PTP1B null mice with partial hepatectomy, liver regeneration is enhanced due to activated EGFR signaling pathways (457).…”
Section: Role Of Egfr In the Livermentioning
confidence: 99%
“…Another potential mediator is the phosphatase PTP1B that binds Met and EGFR and decreases their activation. PTP1B deficiency results in enhanced EGF‐ and HGF‐mediated signalling in hepatocytes and livers submitted to partial hepatectomy resulting in accelerated regeneration, and also confers resistance on TGF‐β‐induced suppressor effects in hepatocytes . Whether the effects on tyrosine kinase receptors and TGF‐β signalling are mutually dependent has not been clarified.…”
Section: The Tgf‐β As a Guardian Of Liver Homeostasismentioning
confidence: 99%
“…There is a growing body of evidence to suggest that PTP1B inhibitors hold great promise for the treatment of type 2 diabetes as well as cancer [3,4,8,[16][17][18][22][23][24][25][26][27][28][29][30]. Numerous mouse and human studies have demonstrated that decreasing PTP1B in various tissues including muscle, liver and brain leads to a multitude of beneficial effects [17,18,22,31].…”
Section: Discussionmentioning
confidence: 99%